2015
DOI: 10.5935/0103-5053.20150354
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Catalysts for C-C and C-O Hydrogenolysis: Catalytic Consequences of Iridium Sites

Abstract: The support effect on the properties of iridium catalysts for C-C and C-O hydrogenolysis was investigated. Cyclohexane conversion and glycerol hydrogenolysis were used to compare the behavior of iridium catalysts in terms of C-C and C-O cleavage. The nature of the support influenced the catalyst performance in both cyclohexane conversion and glycerol hydrogenolysis. This effect was more evident on the product selectivity. Ir/SiO 2 catalyst presented the highest cyclohexane hydrogenolysis activity and the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Moreover, the main reaction product propylcyclohexane was also present in the gas phase. These data are supported by a known ability of Ir/γ-Al 2 O 3 to catalyze hydrogenolysis of cyclohexane at 260 °C in the gas phase . When comparing the current results with the gas phase composition obtained in HDO of eugenol over Ru/C, it can be seen that methane and C9–C13 hydrocarbons were also observed by Bjelic et al Thus, selection of the metal is crucial for formation of C4 to C6 hydrocarbons observed in the current work.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the main reaction product propylcyclohexane was also present in the gas phase. These data are supported by a known ability of Ir/γ-Al 2 O 3 to catalyze hydrogenolysis of cyclohexane at 260 °C in the gas phase . When comparing the current results with the gas phase composition obtained in HDO of eugenol over Ru/C, it can be seen that methane and C9–C13 hydrocarbons were also observed by Bjelic et al Thus, selection of the metal is crucial for formation of C4 to C6 hydrocarbons observed in the current work.…”
Section: Resultssupporting
confidence: 88%
“…Because the IRA-1 catalyst was only very mildly acidic ( Table 7 ), acidity was not the origin of a low GCLPA. This catalyst contained, however, well dispersed Ir, which might be a reason for its high hydrogenolysis activity 47 providing low GCLPA. According to XPS analysis, IRA-1 in addition contained also Re 4+ , which was not present in IRA-3.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out here, that these compounds did not elute from the same GC column in quantitative GC analysis in this study. Since Ir can promote according to the literature hydrogenolysis, it was decided to explore catalytic activity of highly dispersed iridium supported on non‐acidic silica in deoxygenation of dihydroeugenol.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this work was to investigate kinetics in HDO of isoeugenol over bifunctional Pt‐ and Ir‐modified H‐Beta catalysts with different acidity and compare their performance with Pt and Ir supported on MCM‐41, since mesoporosity can have beneficial effects in HDO of phenolic compounds . Ir can also be beneficial in HDO, since it is known to exhibit hydrogenolysis activity . In addition mildly acidic Pt/Al 2 O 3 and non‐acidic Ir/SiO 2 were also studied in order to elucidate the role of acidity, support structure and metal in HDO of eugenol.…”
Section: Introductionmentioning
confidence: 99%
“…S. Ahmed, O. Y. Abdelaziz, G. W. Roberts † catalysts [27]. It is worth noting that the reactivity of glycerol and reaction intermediates on iridium catalysts are extensively affected by the nature of the adopted support [28].…”
mentioning
confidence: 99%